Pola Pemberdayaan Terhadap Pengembangan Kreativitas Dan Keterampilan Tahfidz Anak di Panti Asuhan Muhammadiyah Lima Kaum Kabupaten Tanah Datar - Fatimah Azzahra; Rahma Wati; Beni Putra Hanafi (Empower : Jurnal Pengembangan Masyarakat Islam, 2021)
The children who live in the orphanage are not all orphans, but there are some children who are being cared for due to lack of financial funds to get an education. There are various problems in the lives of foster children, ranging from social problems, psychological problems, and religious problems. One of the solutions provided by the orphanage is to provide an approach to strengthening religious guidance in the form of memorizing the Al-Quran which is guided by the caregivers at the orphanage. This Al-Quran memorizing activity, apart from being a religious guidance activity, is also a means to take a psychological approach to children with religious values. The research method that the researchers did was qualitative descriptive research. This study uses a qualitative approach. Efforts to EmpowerChildren Through Memorizing Al-Quran Activities at the Muhammadiyah Lima Kaum Orphanage in Tanah Datar Regency are carried out by the foundation, namely with the target of memorizing 3 juz of Al-Quran in 3 years, providing caregivers for foster children, and also providing Al-Quran facilities that help foster children in memorizing and applying rules and regulations and are also given rewards or prizes to facilitate children's memorization.